Labour Underutilisation in the BRICS-4: Do Exchange Rates and Foreign Direct Investment Matter? - Tri Wahyuni; Eogenie Lakilaki; Panca Wijaya; Anisha Anisha (Forum Kerjasama Pendidikan Tinggi, 2026)
This study aims to examine unemployment dynamics in BRICS-4 countries (Brazil, India, China, and Indonesia), with a particular emphasis on the effects of foreign direct investment and exchange rates within the framework of sustainable development. The primary issue addressed is the persistently high level of unemployment despite positive trends in economic growth and foreign investment inflows. A quantitative approach is employed using panel data analysis covering the period 2009–2023, in which all variables are transformed into natural logarithmic form to stabilise data variance. Model selection is conducted through the Chow, Hausman, and Lagrange Multiplier tests, which indicate that the Fixed Effects model represents the most appropriate estimation technique. The analysis encompasses classical assumption testing, partial and simultaneous significance tests, as well as the coefficient of determination. The novelty of this study lies in its cross-country integration of unemployment, foreign direct investment, and exchange rate variables within a sustainable development perspective. The empirical results demonstrate that foreign direct investment exerts a negative and statistically significant effect on unemployment, with a coefficient value of −0.12 and a probability value of 0.02, while the exchange rate exhibits a positive effect of 0.06 but remains statistically insignificant, as reflected by a probability value of 0.49. These findings underscore the critical role of foreign investment in employment generation and suggest that the influence of exchange rates is indirect and contingent upon the structural characteristics of individual countries.